P08.29 Web-tool to assess the cost-effectiveness of chlamydia point-of-care tests at the local level. (13th September 2015) - Harding-Esch, E; Sherrard-Smith, E; Dangerfield, C; Choi, YH; Green, N; Jit, M; Marshall, RD; Mercer, C; Nardone, A; Howell-Jones, R; Johnson, OA; Clarkson, J; et al.
Abstract : Introduction: Point-of-care tests (POCTs) can eliminate the delay between being tested for chlamydia and receiving the result and treatment, potentially reducing loss to follow-up. However, the cost-effectiveness of POCT implementation depends on multiple factors, including cost-per-test, clinic time, sensitivity and specificity, and the epidemiological impact of POC testing on transmission. Decision-makers consider a complex range of information when determining potential impact of introducing a POCT. To enable commissioners, providers, POCT manufacturers and others to assess the advantages, disadvantages and uncertainty of POCTs for chlamydia in different local settings, we developed a user-friendly web-based tool (POCTiC): www.poctic.uk.net Methods: The web-tool is underpinned by a transmission-dynamic model for chlamydia, which uses behavioural and prevalence data from the National Survey of Sexual Attitudes and Lifestyle (Natsal), and reproduces local coverage and diagnosis rates from Public Health England datasets. A user group consisting of industry, sexual health facilitators, sexual health commissioners, clinicians, public health experts, and healthcare consultants, provided input throughout. The model is pre-run, but certain variables (e.g. costs) are user-determined. Results: Users can estimate changes in the number of infections and diagnoses occurring under different scenarios, with uncertainty ranges. This allows total costs, and cost per infection averted, to be calculated, while accommodating the considerable variation in chlamydia testing coverage, positivity, and diagnosis rates observed at the local level across England. The epidemiological impact of POC testing is dependent on both test performance characteristics and assumptions about the implementation of the test across local services. Conclusion: This tool enables the uncertainties surrounding chlamydia epidemiology and screening implementation to be explored. It also complements local and national knowledge, and contributes to local-level management of chlamydia infection. Users can use the tool to determine the epidemiological impact and cost-effectiveness of implementing POCTs in a particular setting. Disclosure of interest statement: This work was funded by Innovate UK. Additional thanks are given to the UK Medical Research Council, the National Institute for Health Research and the Electronic Self-Testing Instruments for Sexually Transmitted Infection (eSTI 2 ) Consortium funded under the UKCRC Translational Infection Research (TIR) Initiative supported by the Medical Research Council (Grant Number G0901608). The funding sources had no involvement in the study design or conduct; the collection, analysis and interpretation of data; the preparation, review or approval of the manuscript; or the decision to submit the manuscript for publication. The views expressed are those of the authors and not necessarily those of the NHS, the NIHR, the Department of Health, or Public Health England. CED was employed for part of the project by the National Chlamydia Screening Programme. Atlas Genetics Ltd. develop POCTs for STIs. EHE, CL, STS and CAG have received funding from Atlas Genetics Ltd. for performance evaluations of STI POCTs. The other authors declare no competing interests.